PRAKTIK RADD DALAM HUKUM WARIS ISLAM - Muhammad Riyan; M. Islahuddin; Mimin Rohimin (Justicia Religia, 2025)
This study discusses the practice of Radd in Islamic inheritance law, which is a method of settling residual inheritance when there are no ashabah. This study uses a qualitative approach with the library research method to analyze the radd concept from a historical perspective, its conditions and calculation methods. The results of this study show that radd occurs when there is residual property after distribution to ashabul furudh and there is no heir to the ashabah. There are differences of opinion among scholars regarding radd, such as the opinion of Zaid bin Tsabit who handed over the remaining wealth to Baitul mal, Uthman bin Affan who distributed to all ashabul furudh including husbands/wives, and Umar bin Khattab and Ali bin Abi Talib who only gave the heirs of nasabiyah, Ibn Abbas almost the same as the settlement of the third group, That is, not giving radd to the heirs of the sababiyah. However, he did not give radd to the grandmother. This article also presents an example of a radd calculation based on this opinion. A comprehensive understanding of radd is needed to ensure fairness in the distribution of inheritance according to Islamic law.